The Effect of ASYIK Model Song Music Instruments on Early Childhood Learning Spirit - Sudarto, Sudiaryati; Watini, Sri (Kirana Publisher (KNPub), 2025)
This research is an experimental study that aims to determine whether there is an effect of giving ASYIK song music instruments on the enthusiasm for early childhood learning. The research design used in this study is the observation of 2 class groups by looking at the difference between the class that is given treatment, namely the ASYIK song music instrument, and those that are not given treatment. The population in this study included four Group B classes at Al-Fath Kindergarten in the 2024/2025 academic year, totaling 104 students. The research sample included 26 students of class B1 as the experimental group, 26 students of class B2 as the control group, and 26 students of class B3 as the validity test class. There are two data collection techniques used in this study, namely observation and documentation. The analysis technique used includes hypothesis testing using the t-test processed using SPSS version 25. It can be seen that the enthusiasm of children's learning with equal variance not assumed is 9.577 with a probability of 0.001. Because the probability for a two-sided test (0.001 / 2 = 0.0005) < 0.005, then Ho is rejected, or both the average (mean) of the learning spirit of children who are given ASYIK musical instruments with the learning spirit of children who are not given ASYIK musical instruments is higher than children who are not given ASYIK musical instruments.